2005
DOI: 10.1007/s00232-005-0770-7
|View full text |Cite
|
Sign up to set email alerts
|

The Hormonal Control of Uterine Luminal Fluid Secretion and Absorption

Abstract: The secretion of uterine luminal fluid initially provides a transport and support medium for spermatozoa and unimplanted embryos, while the absorption of uterine luminal fluid in early pregnancy results in the closure of the lumen and allows blastocysts to establish intimate contact with the uterine epithelium. We have established an in vivo perfusion technique of the lumen to study the hormonal control of the events in the peri-implantation period. Fluorescein-labelled dextran was included in the perfusion me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 72 publications
3
95
2
2
Order By: Relevance
“…These results are not in agreement with previous reports of humans in which administration of dyes (such as Fluorescein, Methylene Blue, or Evans Blue) directly into the amniotic sac demonstrated discoloration of the fetal skin that can be detected up to 2 weeks after the injection is administered [36,37]. The discrepancy of these results might be due to different absorption rates inter species with a more rapid absorption of the dyes by the rodent uterus [38][39][40]. In fact, preliminary experiments in our lab of intra-amniotic injection of dyes at day 15 of gestation and then harvesting fetuses at different time points, have demonstrated that the fetal skin was stained right after injection (data not shown).…”
Section: Discussioncontrasting
confidence: 57%
“…These results are not in agreement with previous reports of humans in which administration of dyes (such as Fluorescein, Methylene Blue, or Evans Blue) directly into the amniotic sac demonstrated discoloration of the fetal skin that can be detected up to 2 weeks after the injection is administered [36,37]. The discrepancy of these results might be due to different absorption rates inter species with a more rapid absorption of the dyes by the rodent uterus [38][39][40]. In fact, preliminary experiments in our lab of intra-amniotic injection of dyes at day 15 of gestation and then harvesting fetuses at different time points, have demonstrated that the fetal skin was stained right after injection (data not shown).…”
Section: Discussioncontrasting
confidence: 57%
“…Uterine luminal closure fails to occur in mice missing FK506 binding protein-4 (FKBP52), a co-chaperone for full progesterone receptor (PR) function (Tranguch et al, 2005a). Recent evidence shows that cystic fibrosis transmembrane conductance regulator (CFTR) and epithelial Na + channel (ENaC) are the major gatekeepers regulating uterine fluid secretion and reabsorption (Salleh et al, 2005). Activation of ENaC is required for prostaglandin synthesis and release, which has been proven to be critical for embryo implantation (Ruan et al, 2012).…”
Section: Luminal Closurementioning
confidence: 99%
“…In the uterus, only ␣ENaC was detected, and expression varied with the estrus cycle and inversely to the expression of CFTR (74). Increased fluid absorption during periods when ENaC expression is increased may be required to facilitate blastocyst implantation (335,427). Postimplantation, uterine expression of ENaC gradually declines (74).…”
Section: Enac In the Gut And Reproductive Systemsmentioning
confidence: 99%